PENETAPAN STANDARD KOMPETENSI PERFORMANCE STANDARD SETTING - Hartini, Sri (Joglo, 2009)
ABSTRACTstandard is meant the answer of "how god is enough". In the filed of education (teaching and learning). passing point or cut score is a common terminology/concept. It is used as a standard to determine one's achievement (success). Standard is devided into academic content standard and performance standard. The former means what is supposed to know and to do by students. Where as the latter concorns how far students master knowledge and skills. There are three methods of setting performance standard(1) Nedelsky,(2) Angoff, (3) Ebel. The three methods are based on the fact that there is a group of students that belongs to border line. Based on the above explanation, it is concluded as follows : (1)passing point (cut score) is needed to determine student's competence for the sake of certification :(2) The standard is based on border-line student:(3) There is no best method. Method is determined by appropriatness due to certain/specific condition required.keyword : Performance and Standard Setting